Re-Democratization in Chile: Is the “New” Democracy Better Than the “Old”? - Olavarria-Gambi, M (Routledge, 2023)
Much of the literature on democratic transitions has focused on the transition from authoritarianism to democracy, but few studies have examined how democracies that re-emerged compare to those that existed in the past. Examining the Chilean case, this study explores the degree to which the “new” democracy has recovered its former strength, posing a similar question for other Latin American countries. It considers the conceptualization of quality of democracy that underpins this controversy and explores the methodological challenges of intertemporal comparison, which may be relevant for other cases that have experienced periods of authoritarian rule and process of re-democratization. We find that, overall, democracy in the contemporary period is more robust. Yet, to an important extent, indices’ different understandings of the concept of the quality of democracy are relevant in terms of the degree to which they emphasize procedural aspects versus democratic outcomes. © 2021 Taylor & Francis Group, LLC.